Development of project management of the region’s Economy - R. R. Siyukhov; S. K. Chinazirova; R. V. Kostenko (Новые технологии, 2022)
Currently, economic progress requires solving a number of interrelated tasks in the constituent entities of the Russian Federation. A significant part of them concerns the problem of the effective use of the potential of enterprises and organizations, functioning in various sectors and spheres of the national economy. Consequently, appropriate project management processes in the region are needed to realize the economic potential. The problem of the study is how project management affects the development of the region, the solution of which is of significant practical and theoretical interest for the economy of the region. The purpose of this article is to search for and substantiate approaches to improving the development processes of project management in the economy of the region. The following methods of scientific cognition are used in the work: abstraction, analysis, induction, synthesis. The article discusses the methodology of project management, the budget of national projects of the Russian Federation and its structure. The system of state regulation of the development of the region’s economy has been studied. The relevance of using the tools of project management of the region’s economy is substantiated. In addition, the factors influencing the formation of the state strategy in the regional context are presented. New tools for the development of project management of the region’s economy are considered, such as: «Waterfall», «Agile», «Scrum», the critical path method (CPM), critical project chain management Critical Chain PM (CCPM). It is proved that the use of regional policy instruments largely depends on the potential of regions, territorial differences in their development, the specifics of regional problems, the degree of decentralization of public administration.